2006
DOI: 10.1038/sj.onc.1209815
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB activation by combinations of NEMO SUMOylation and ATM activation stresses in the absence of DNA damage

Abstract: The inactive transcription factor NF-jB is localized in the cytoplasm and rapidly responds to a variety of extracellular factors and intracellular stress conditions to initiate multiple cellular responses. While the knowledge regarding NF-jB signaling pathways initiated by extracellular ligands is rapidly expanding, the mechanisms of activation by intracellular stress conditions are not well understood. We recently described a critical role for a small ubiquitin-like modifier (SUMO) modification of NF-jB essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 64 publications
1
50
2
Order By: Relevance
“…Genotoxic insults causing DNA DSBs induce SUMOylation of NEMO resident in the nucleus, blocking its export. Concomitantly, activated ATM allows removal of SUMO residues from NEMO, permitting NEMO ubiquitination (20,68). The ATM-ubiquitinated NEMO complex then migrates to the cytoplasm, where it activates the IKK complex, leading to RelA nuclear transport and culminating in the induction of NF-B-responsive genes.…”
Section: Discussionmentioning
confidence: 99%
“…Genotoxic insults causing DNA DSBs induce SUMOylation of NEMO resident in the nucleus, blocking its export. Concomitantly, activated ATM allows removal of SUMO residues from NEMO, permitting NEMO ubiquitination (20,68). The ATM-ubiquitinated NEMO complex then migrates to the cytoplasm, where it activates the IKK complex, leading to RelA nuclear transport and culminating in the induction of NF-B-responsive genes.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that LBH-589 causes nuclear localization of NEMO and promotes its interaction with ATM in an oxidative stress-dependent manner. Oxidative stress can activate ATM [84] and cause SUMOylation of NEMO [57]. NF-κB activation by LBH-589 is inhibited in cells expressing SUMOylation-defective NEMO-DK (K277A/ K309A) mutant [83].…”
Section: Atm-nemo Signaling In Oxidative Stressmentioning
confidence: 99%
“…For example, activation of NF-κB as measured by electrophoretic mobility shift assay by DSB inducers is readily detectable in various cell lines, such as HEK293 embryonic kidney fibroblasts, HeLa cervical cancer, U2OS osteosarcoma, CEM T leukemic and 70Z/3 pre-B leukemic cells, among others [52,55,57,60,64,66,68]. In contrast, NF-κB activation by VP16 or IR in primary MEFs and MEF lines, or many human normal cell types, is frequently undetectable or only weakly detected even at relatively high doses, despite efficient ATM activation [11,55,59,64,68].…”
Section: Additional Nf-κb Signaling By Genotoxic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions were terminated with a solution containing EDTA, sodium dodecyl sulfate (SDS) and bromophenol blue, and the samples were run on a non-denaturing 6% polyacrylamide gel and imaged by autoradiography (Byun et al, 2002;Wuerzberger-Davis et al, 2007).…”
Section: Electrophoretic Mobility Shift Assaymentioning
confidence: 99%